Italian hybrid diplomacy. Issue 2 (4th May 2018) - Marchetti, Raffaele
ABSTRACT: The text offers a new assessment of Italy's contribution to international affairs. Through a more pluralist interpretation of Italian action at international level it is possible to outline an image of Italy as a normative power able to influence the formulation of the principles that determine what is legitimate at international level. Italy's contribution in recent decades has been crucial in a series of transnational campaigns that have had a significant impact globally. These cases illustrate the role played by Italy in the politics of changing international norms related to human rights. The mobilisations have been the result of a combination of factors, including the intense synergy that has been established between the actions of the Italian government and Italian civil-society organisations. This study analyses eight cases in which such synergy has been positive, leading to a significant impact of Italian hybrid diplomacy on international politics.